Morphological variability and state of population of the zeravshan dace Leuciscus lehmanni (Сypriniformes; Actinopterygii) from the Shayan river (the Syrdarya river basin) (Eurasian Journal of Ecology, 2023)
Human made ecological crisis in the basin of Aral Sea has gone strong negative impact to the native fish fauna.  The tributaries of the Syrdarya River turned out to be natural shelters for many non-commercial fish species. The objectives of our study were to study morphological variability and assess the state of the dace population inhabiting the Shayan River. Fish for study were caught in 2013 and 2020. Based on the analysis of external signs, the belonging of the fish to the Zeravshan dace species Leuciscus lehmanni Brandt, 1852 was established. Morphological and biological analyzes of fish were carried out according to the widely used method. The variability of 32 plastic and 18 counting traits, size and weight indicators, fatness, fat content, growth and food objects was studied. Differences in the appearance of individuals may be the result of the implementation of different life strategies in a heterogeneous environmental conditions. For the first time, data on morphological variability, growth and nutrition of the Zeravshan dace were obtained for the water bodies of the Republic of Kazakhstan. In the samples of 2013 and 2020, individuals of different ages were represented. The limits of body size variability coincide, which indicates sufficient conditions for reproduction and existence. In 2013, the sample was dominated by larger individuals, fatness, intestinal filling and fat content were higher than in 2020. Food objects do not change over the years. The intestines of fish from both samples contain detritus, green algae, aquatic insect larvae, and adults of terrestrial insects (Hymenoptera and Diptera). In 2020, some deterioration of feeding happened, which led to a decrease in the reserves of abdominal fat and body condition coefficients of fish. Also in 2020, the violation of the homeostasis of individual development increased.Key words: Zeravshan dace, Leuciscus lehmanni, морфология, биология, изменчивость, Сырдарьинский бассейн, Каратау.